DETERMINATION OF PAYMENT OF TAX OBJECTS IN THE DEED OF LEASE AGREEMENT FOR THE MANAGEMENT OF TOURISM OBJECTS MADE BY A NOTARY - Rizqy Miftahul Huda; Rahmatul Hidayati; Ahmad Siboy (SOSIOEDUKASI, 2026)
This study examines the determination of tax obligations in lease agreements for the management of tourism objects, focusing on the Cooperation Agreement for the Utilization of the Pantai Bentar Tourism Object. The research aims to analyze the legal regulation of tax object payment, the legal consequences of the absence of taxation clauses, and the notary’s responsibility when the deed does not clearly stipulate the parties’ rights and obligations. This study employs a normative juridical method using statutory and conceptual approaches, with legal materials collected through library and document research on regional asset management, taxation, and notarial law. The findings indicate that although the agreement formally fulfills the requirements of Article 1320 of the Indonesian Civil Code, it substantively fails to comply with mandatory legal norms due to the absence of taxation clauses and clear allocation of rights and obligations. This omission violates prevailing fiscal regulations and may cause legal uncertainty and potential regional financial losses. The study concludes that notaries bear professional and administrative responsibility to ensure that authentic deeds comply with mandatory public law provisions to guarantee legal certainty in regional asset management.